A Trip to the SCIENCE MUSEUM with SESAME STREET - Peterson, Christy (Minneapolis : Lerner Publications Company, 2022)
"Elmo and Sesame Street friends take readers on a tour of a science museum. Readers learn about math, technology, and how to make observations"-- Provided by publisher.
Includes index.
Keywords: Science museums -- Juvenile literature